Cognitive task analyses for decision centred design and training. - O'hare D; Wiggins M; Williams A; Wong W (Ergonomics)
This paper presents three case studies of Cognitive Task Analysis (CTA) for defining systems design and training requirements. The approach taken involves a modification of the critical decision method of Klein et al . The authors utilized the revised CDM to obtain information from expert white-water rafting guides, general aviation pilots, and emergency ambulance dispatchers. The information obtained was used to develop multi-media tools for training rafting guides and general aviation pilots, and to redesign the VDU display requirements for the ambulance dispatchers. The examples demonstrate the utility of an approach to CTA that is closely based on relevant theory, and provides guidance to practitioners wishing to apply CTA techniques.